1997
DOI: 10.1042/bj3260661
|View full text |Cite
|
Sign up to set email alerts
|

Heparin inhibits the binding of basic fibroblast growth factor to cultured human aortic smooth-muscle cells

Abstract: Basic fibroblast growth factor (bFGF) and its specific receptors have diverse roles on a variety of cell types, such as the induction of vascular smooth-muscle cell proliferation which contributes to restenosis after coronary balloon angioplasty. bFGF is also known to interact with heparan sulphate proteoglycans present on the cell surface or in the extracellular matrix. In this study, the binding of 125I-bFGF to human aortic smooth-muscle cells was investigated. 125I-bFGF binding to these cells was reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…[51,52] However, high concentrations of heparin inhibit the proliferation of smooth muscle cells. [53] The bFGF bioactivity from PEUU scaffolds without heparin indicated that commonly-used growth factor stabilizing protein BSA [20] alone could stabilize the bFGF and maintain smooth muscle cell mitogenicity. The incorporation of heparin may further stabilize the bFGF, but our data did not suggest such stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51,52] However, high concentrations of heparin inhibit the proliferation of smooth muscle cells. [53] The bFGF bioactivity from PEUU scaffolds without heparin indicated that commonly-used growth factor stabilizing protein BSA [20] alone could stabilize the bFGF and maintain smooth muscle cell mitogenicity. The incorporation of heparin may further stabilize the bFGF, but our data did not suggest such stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Scaffolds loaded with 100 ng bFGF /mg PEUU (without I 125 -bFGF) were cut into 50 mg pieces. Samples were placed into a 15 mL conical tube and 10 mL release medium was added.…”
Section: Bioactivity Of Released Bfgfmentioning
confidence: 99%
“…Heparin inhibits growth of baboon SMCs by preventing prolonged mitogen-activated protein kinase activation elicited by ligands of seven transmembrane domain receptors and heterotrimeric G-proteins (39). Bono et al (40) showed that heparin inhibits the binding of basic fibroblast growth factor to cultured human aortic SMCs. Lake and Castellot (41) showed that Wnt-induced secreted protein-2 modulates the antiproliferative effect of heparin and regulates cell motility in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between heparin and proteins can vary from highly sequence specific, such as the binding of AT, to relatively nonspecific (Mulloy et al, 1996) (see section III); hence, a wide array of physiologically relevant molecules are bound by this highly polyanionic molecule (Tyrrell et al, 1999; Table 1). A significant number of proteins that can be classed as heparin binding are fundamentally associated with the inflammatory response, including, but by no means limited to, cytokines (Muramatsu and Muramatsu, 2008), chemokines (Miller and Krangel, 1992;Handel et al, 2005;Shute, 2012), growth factors (Skinner et al, 1991;Watt et al, 1993;Diamond et al, 1995;Bono et al, 1997;Koenig et al, 1998), adhesion molecules (Lever et al, 2000), cytotoxic peptides (Fredens et al, 1991), and tissue-degrading enzymes (Redini et al, 1988;Walsh et al, 1991).…”
Section: Non-anticoagulant Effects Of Heparinmentioning
confidence: 99%